Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How would I verify the following double angle identity. $$ \sin(A+B)\sin(A-B)=\sin^2A-\sin^2B $$ So far I have done this. $$ (\sin A\cos B+\cos A\sin B)(\sin A\cos B-\cos A\sin B) $$But I am not sure how to proceed.

share|cite|improve this question

\begin{eqnarray} \sin(A+B)\sin(A-B) &=& (\sin A\cos B+\cos A\sin B)(\sin A\cos B-\cos A\sin B)\\\\ &=& \sin^2 A \cos^2 B -\sin^2 B \cos^2 A\\\\ &=& \sin^2 A \cos^2 B -\sin^2 B (1-\sin^2 A)\\\\ &=& \sin^2 A (\cos^2 B + \sin^2 B) - \sin^2 B\\\\ &=& \sin^2 A - \sin^2 B \end{eqnarray}

share|cite|improve this answer
It makes sense.Thank you. – El Bananero Jul 25 '12 at 17:47
$$\sin^2 A \cos^2 B -\sin^2 B \cos^2 A=\sin^2 A(1- \sin^2 B) -\sin^2 B (1-\sin^2 A)=?$$ – lab bhattacharjee Aug 28 '15 at 9:19

$$ \begin{align*}\sin (A+B)\cdot\sin (A-B)&=\frac{\cos(2B)-\cos (2A)}{2}\\&=\frac{(1-2\sin^2B)-(1-2\sin^2A)}{2}\\&=\sin^2A-\sin^2B\end{align*}$$

Here i have used $$\sin x\cdot\sin y=\frac{\cos(x-y)-\cos(x+y)}{2}$$

share|cite|improve this answer

Hint: $(a+b)(a-b)=a^2-b^2$.
Then use $\sin^2\theta+\cos^2\theta=1$

share|cite|improve this answer
Do you mean I would do (sinA-sinB)(SinA+sinB)? – El Bananero Jul 25 '12 at 17:38
No, $a=\sin A \cos B$ and $b=\sin B \cos A$ – Saurabh Jul 25 '12 at 17:40
Oh I see thanks. – El Bananero Jul 25 '12 at 17:47

use this formula

$$ 2 \sin(A+B)\sin(A-B)=\cos2B-\cos2A $$

it will like this

$$ \dfrac12 \cdot (\cos2B-\cos2A) $$ $$ \dfrac {(1-2\sin^2B)-(1-2\sin^2A)}{2} $$

it will give answer

share|cite|improve this answer

Open the bracket of what you got and substitute every cos^2 with 1-sin^2 and open bracket again. Thats it...

share|cite|improve this answer

Your question involves the basic algebra identity which says, $(a + b)(a - b) = a^2 - b^2 $. For targeting your question, it is easy to assume $ a = \sin A\cos B $ and $b = \cos A \sin B$. The process becomes easy now.

$$\begin{align}(a + b)(a - b)& =& a^2 - b^2\\ & = & (\sin A \cos B)^2 - (\cos A \sin B)^2\\ & = & \sin^2A\cos^2 B - \cos^2A\sin^2B \\ & = & \sin^2A(1 - \sin^2 B) - \cos^2 A\sin^2B \end{align} $$Proceed.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.